2014
DOI: 10.1002/jnr.23379
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CXCL2 upregulation underlies the therapeutic effect of the retinoid Am80 on intracerebral hemorrhage in mice

Abstract: We previously demonstrated that a synthetic retinoic acid receptor agonist, Am80, attenuated intracerebral hemorrhage (ICH)-induced neuropathological changes and neurological dysfunction. Because inflammatory events are among the prominent features of ICH pathology that are affected by Am80, this study investigated the potential involvement of proinflammatory cytokines/chemokines in the effect of Am80 on ICH. ICH induced by collagenase injection into mouse striatum caused prominent upregulation of mRNAs for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…Poststroke neuropathic pain is common among 2-8% of patients [55]. ICH and intracerebral blood involve in activation of resident microglia, infiltration of immune cells and subsequent production of cytokine (TNF-α and interleukin (IL)-1β) [6], chemokines [56], extracellular proteases and reactive oxygen species [57,58]. Expression of MMPs is also increased in neurological diseases by inflammation and cell death, particularly in ICH [59].…”
Section: Discussionmentioning
confidence: 99%
“…Poststroke neuropathic pain is common among 2-8% of patients [55]. ICH and intracerebral blood involve in activation of resident microglia, infiltration of immune cells and subsequent production of cytokine (TNF-α and interleukin (IL)-1β) [6], chemokines [56], extracellular proteases and reactive oxygen species [57,58]. Expression of MMPs is also increased in neurological diseases by inflammation and cell death, particularly in ICH [59].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of brain tissue has indicated that chemokine receptors and their downstream effector molecules were activated after ICH [18]. In a collagenase injection ICH model, prominent upregulation of mRNAs for CXCL1, CXCL2, and CCL3 was observed [19]. In 85 patients with ICH, higher CCL2 levels at 24 h were independently associated with poor functional outcome at day 7 [20].…”
mentioning
confidence: 97%
“…Moreover, when we administered reparixin, an antagonist at chemokine receptors CXCR1/CXCR2, we observed a significant recovery of motor performance of mice after ICH in the internal capsule. 25) These results suggest that CXCL2 plays an important role in the pathogenic events in ICH with axonal tract injury.…”
Section: Exploration Of Drugs For Ich With Axonal Tract Injurymentioning
confidence: 84%
“…27) Neutrophil infiltration into tissues can be promoted by several kinds of chemotactic factors including CXCL2. Although we have demonstrated a therapeutic effect of a CXCR antagonist reparixin on the basis of motor performance, 25) the precise modes of action of this drug such as those on neutrophil infiltration and axonal tract injury should be elucidated by further investigations. We should also note here that ICH may be accompanied by increases in several other factors that stimulate neutrophil chemotaxis into the brain.…”
Section: Neutrophils In Axonal Tractmentioning
confidence: 90%
See 1 more Smart Citation